Translation of Positive Emotion Words in Red Queen - Utara, Kadek Gangga; Rajeg, I Made; Puspani, Ida Ayu Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 29 No 1 (2022): MaretDO - 10.24843/ling.2022.v29.i01.p09, 2022)
Abstract-- This study aims to identify and analyze the types of positive emotion and the technique of translation applied to translate the positive emotion words found in the novel Red queen. The method of collecting data in this study was conducted through a documentary method. Furthermore, descriptive qualitative method was applied for analyzing the data. The theories of category of emotions concept and technique of translation were used to analyze the data. There are three types of positive emotion found in the novel. Moreover, only four out of eighteen techniques of translation applied in the novel including literal, amplification, transposition, and particularization.   Keywords: positive emotion words; types of positive emotion; translation technique